Implementation of Community Asset-Based Reverse Osmosis Technology for Independent Access to Clean Water in Bibiosi Village - Rumbiak, Helmin; Katarina Tuturop; Sara Marlyn Paru; Vicky Adi Saputra Saleki; Gabe Obelom Yikwa (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The limited access to clean, consumable water in Bibiosi Village, Keerom Regency, which directly correlates with the high prevalence of environment-based diseases, forms the background of this community service activity, which aims to improve clean water access and community health quality through the implementation of Reverse Osmosis (RO) technology. This activity adopted the Asset-Based Community Development (ABCD) method by mobilizing the potential of the “Narwastu” workers' group as a local asset and primary partner. The program implementation, located in Bibiosi Village, involved 50 heads of households and focused on a series of participatory stages, including socialization to build collective awareness, intensive technical training on the operation and maintenance of the RO unit for 10 members of the “Narwastu” group as technology cadres, and the collaborative installation of the technology unit. The results of the activity show a highly positive and measurable impact, marked by a significant 92% increase in the community's understanding of the urgency of clean water, based on pre-test and post-test analysis, which created a strong social foundation for technology adoption. Furthermore, the program successfully formed competent local technology cadres, with 85% of them proven to have mastered the operational and basic maintenance skills of the RO unit, and successfully installed one water purification unit that is now fully operational and communally accessible to all residents. This activity concludes that the integration of appropriate technology intervention with a community asset-based empowerment approach is a highly effective strategy not only for providing physical infrastructure but also for building community self-reliance and a sense of ownership, which are essential foundations for the sustainability of health and quality of life improvement programs in disadvantaged regions.